Elderly versus nonelderly patients with invasive aspergillosis in the ICU: a comparison and risk factor analysis for mortality from the AspICU cohort. (8th December 2017) - Matthaiou, D K; Dimopoulos, G; Taccone, F S; Bulpa, P; Van den Abeele, A M; Misset, B; Meersseman, W; Spapen, H; Cardoso, T; Charles, P E; Vogelaers, D; Blot, S; et al.
Abstract: Data regarding the epidemiology and diagnosis of invasive aspergillosis in the critically ill population are limited, with data regarding elderly patients (≥75 years old) even scarcer. We aimed to further compare the epidemiology, characteristics and outcome of elderly versus nonelderly critically ill patients with invasive aspergillosis (IA) Prospective, international, multicenter observational study (AspICU) including adult intensive care unit (ICU) patients, with a culture and/or direct examination and/or histopathological sample positive for Aspergillus spp. at any site. We compared clinical characteristics and outcome of IA in ICU patients using two different diagnostic algorithms. Elderly and nonelderly ICU patients with IA differed in a number of characteristics, including comorbidities, clinical features of the disease, mycology testing, and radiological findings. No difference regarding mortality was found. According to the clinical algorithm, elderly patients were more likely to be diagnosed with putative IA. Elderly patients had less diagnostic radiological findings and when these findings were present they were detected late in the disease course. The comparison between elderly survivors and nonsurvivors demonstrated differences in clinical characteristics of the disease, affected sites and supportive therapy needed. All patients who were diagnosed with proven IA died. Increased vigilance combined with active search for mycological laboratory evidence and radiological confirmation are necessary for the timely diagnosis of IA in the elderly patient subset. Although elderly state per se is not a particular risk factor for mortality, a high SOFA score and the decision not to administer antifungal therapy may have an impact on survival of elderly patients.